ANALISIS PELAKSANAAN TUJUH LANGKAH MENUJU KESELAMATAN PASIEN DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Alifa Rizqia Rachmawati; Putri Asmita Wigati; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Hospital has to design a process,  monitor and evaluate performance, analyze incident intensively in improving its patient safety performance. ‘Seven Steps to Patient Safety’ is a reference for hospitals to implement patient safety program. The objective of this research is to analyze the implementation of Seven Steps to Patient Safety in Sultan Agung Islamic Hospital Semarang. This research is qualitative descriptive research. Data were collected by indepth interview and observation method. The key informants of this research are four Quality Link Safety Champions of four different departments. The result showed that not all steps in Seven Steps to Patient Safety are implemented. There is still blaming culture in departments; the implementation of patient safety is still about collecting data only; mindset is still about only doing the program , not improving the program; lack of management commitment for demonstrating patient safety culture; there are still delays in reporting incident; there is no open communication policy about telling incident to patient and family; and there is no active learning about incident which involving all departments in hospital. Suggestion in this research is hospital need to do a routine meeting and excecutive walkabout which involve excecutive leader, Quality and Safety Committee, and departmens that focuses only about patient safety for demonstrating, enhance patient safety commitment, also improve open and fair patient safety culture.